Mattei Dogan y Stein Rokkan (compiladores). Quantitative Ecological Analysis in the Social Sciences. Cambridge, Mass. : The M.I.T. Press, 1969. xv, 607 p. - Reyna, José Luis (Estudios Demográficos y Urbanos, 1970)
MATTEI DOGAN y STEIN ROKKAN (compiladores), Quantitative Eoological Analysis in the Social Sciences. Cambridge, Mass., The M.I.T. Press, 1969.